Effects of different etching modes on the nanoleakage of universal adhesives: A systematic review and meta‐analysis. Issue 4 (23rd March 2018) - Kaczor, Kinga; Gerula‐Szymańska, Agnieszka; Smektała, Tomasz; Safranow, Krzysztof; Lewusz, Katarzyna; Nowicka, Alicja
Abstract: Purpose: The aim of this systematic review was to evaluate how etching modes affect the nanoleakage of universal adhesive from in vitro studies. Materials and methods: PubMed/MEDLINE, Web of Science, Scopus and Science Direct electronic databases were searched for in vitro studies that evaluated the nanoleakage of universal adhesives. A total of 511 (after duplicate removal) potentially relevant records were identified in the literature search. The titles and abstracts of the retrieved studies were screened by two independent researchers according to the main concept. Subsequently, the full text of potentially relevant studies was screened using the exclusion criteria. Thirteen studies were subjected to qualitative analysis, and 5 of them were selected for a detailed meta‐analysis. Results: Seven universal adhesives were evaluated in this review. The meta‐analysis demonstrated that the etch‐and‐rinse technique significantly reduced the nanoleakage of the Peak Universal and G‐Bond Plus adhesives, whereas the self‐etch mode reduced the nanoleakage of All‐Bond Universal. In comparison, the etching technique did not significantly alter the nanoleakage of either Prime&Bond Elect or Scotchbond Universal which was characterized by the smallest nanoleakage. Conclusions: Etching modes significantly, in various ways, influence the nanoleakage of universal adhesives. Clinical significance: Contrary to the drive to simplify bonding technologies, an appreciation of their adhesive components and how these perform according to bonding technique could yield a knowledge‐based practical approach that ultimately improves the longevity of direct composite restorations.